Dictionary of plant breeding - Schlegel, Rolf H. J. (CRC Press, 2010)
the Dictionary of Plant Breeding contains clear and useful definitions of the terms associated with plant breeding and related scientific/technological disciplines. This second edition of a bestseller defines jargon, provides helpful tables, examples, and breeding schemes, and includes a list of crop plants with salient details. Packed with data and organized to make that data easy to access, this revised and expanded reference provides comprehensive coverage of the latest discoveries in cytogenetics, molecular genetics, marker-assisted selection, experimental gene transfer, seed sciences, crop physiology, and genetically modified crops